PARADIGMA SIRI ORANG BUGIS DALAM CERITA LA WELLE (Siri Paradigm of Buginese People in “La Welle” Story) - Herlina Andi (SAWERIGADING, 2014)
The writing is to describe siri paradigm of Buginese people in La Welle story using structuralism theory of Levi- Strauss. It applies descriptive qualitative method through noting, interviewing technique, and library study. Then, the analysis finds out the description of social-cultural Buginese tribe of sirik that becomes the essence of some one’s life and would be fatal for any one whom disobeys it. Social-economic condition of Buginese people is described as skillful adventurer. Therefore, Buginese people is characterized by brave and wanderer man and having high spirit. Besides strength and skill, emotional and spiritual intelligence must be embedded in sirik building. Keywords: sirik, mythm, synchroni